(Mis)Recognition and changing roles: a lacanian reading of Henry James's the turn fo the screw - Takakura, Sandra Mina (2003)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.